Clinical features and survival analysis of adult patients with severe lower respiratory tract infection positive for respiratory syncytial virus - Jiahua Tian; Ling Zhang; Xunling Wang; Guichuan Huang; Zhu Li; Ling Gong; Daishun Liu (BMC Pulmonary Medicine)
Abstract Background The awareness and attention toward lower respiratory tract infections caused by respiratory syncytial virus (RSV) are lower in adults than in children. Moreover, the clinical data on severe RSV infections in adults are lacking. This study aimed to augment the clinical understanding of RSV infections. Method This study was performed on 191 adult patients with severe lower respiratory tract infections admitted to the intensive care unit (ICU) of Zunyi Medical University Affiliated Hospital (Zhuhai). The sputum specimens were collected for RSV testing, and the clinical data were collected and analyzed statistically. Results The findings revealed that patients in the RSV-positive group were older, had a higher prevalence of underlying diseases, were more likely to require noninvasive mechanical ventilation, and had prolonged hospital stays compared with those in the RSV-negative group. Furthermore, Kaplan–Meier survival analysis conducted within 90 days revealed comparable mortality rates between the RSV-positive and RSV-negative groups. In the RSV-positive group, elderly patients and patients with congestive heart failure or chronic obstructive pulmonary disease had lower survival rates. Conclusion Patients in the RSV-positive group, particularly elderly patients and patients with congestive heart failure or, experience reduced survival durations compared with those in the RSV-negative group.